Effects of Biochar and Organic Fertilizer Application on Soybean Growth Under Melaleuca cajuputi Stand - Nurmalasari, Aprilia Ike; Rahayu, Muji; Sakya, Amalia Tetrani; Purnomo, Djoko; Arviana, Annisa Dian (Fakultas Pertanian Universitas Padjadjaran, 2025)
The production of agricultural commodities is affected by the reduction of productive land, whichis due to the land conversion into residential and industrial areas. Maximizing the potential of dry land with biochar and organicfertilizerapplication can potentiallybecome the solution to overcome it. Biochar functions to retain water and hold nutrients, while organic fertilizer can enhance soil fertility. The research aims to analyze the effects of biochar and organic fertilizers application on soybean growth in agroforestry planting areas. This research was conducted at Menggoran Forest Resort, Playen, Gunungkidul, Yogyakarta, from March to June 2022. The experiment was designed in a factorial randomized complete block design (RCBD) with two factors. The First factor was types of biochar (without biochar, rice husk biochar, coconut shell biochar), and the second factor was types of organic fertilizer (without organic fertilizer, chicken manure, cow manure, and goat manure). The observed variables were leaf area index (LAI), specific leaf weight (SLW), leaf area ratio (LAR), specific leaf area (SLA), crop growth rate (CGR), net assimilation rate (NAR), and soil N-total percentage. The data were analyzed using analysis of variance (ANOVA), and if the treatment showed significant differences, Duncan’s Multiple Range Test (DMRT) at a 5% significance level was performed. The results showed no interaction between the type of biochar and the type of organic fertilizer. The application of biochar and organic fertilizers tested did not increase any of the observed growthparameters.The application of organic fertilizer independently has an effect on the percentage of soil N-total, and cow and goat manure application resulted in significantly higher final soil N-total percentages compared to without organic fertilizer treatment.